2011
DOI: 10.1007/s00134-011-2327-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of recombinant human activated protein C and dexamethasone in experimental septic shock

Abstract: Both APC and Dexa improve arterial contractility and endothelial dysfunction resulting from septic shock in rats. Moreover, their combination increased the length of survival. These findings provide important insights into the mechanisms underlying APC- and/or Dexa-induced improvements of arterial dysfunction during septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…GC-GRα is also strongly involved in vascular development (81). Experimental studies have shown GR-dependent upregulation of multiple mediators involved in endothelial cell homeostasis, such as sphingosine kinase 1 (SphK1) (157), angiopoietin-1 (Angpt-1) (158), serum glucocorticoid kinase-1 (SGK-1) (159,160), GILZ (161), and eNOS (162)(163)(164). In experimental ARDS, upregulation of SphK1, an important regulator of endothelial barrier integrity, was shown to improve alveolo-capillary membrane (ACM) permeability (157).…”
Section: Endotheliummentioning
confidence: 99%
See 1 more Smart Citation
“…GC-GRα is also strongly involved in vascular development (81). Experimental studies have shown GR-dependent upregulation of multiple mediators involved in endothelial cell homeostasis, such as sphingosine kinase 1 (SphK1) (157), angiopoietin-1 (Angpt-1) (158), serum glucocorticoid kinase-1 (SGK-1) (159,160), GILZ (161), and eNOS (162)(163)(164). In experimental ARDS, upregulation of SphK1, an important regulator of endothelial barrier integrity, was shown to improve alveolo-capillary membrane (ACM) permeability (157).…”
Section: Endotheliummentioning
confidence: 99%
“…In murine sepsis, GC treatment attenuated renal dysfunction by reducing mitochondrial injury with preservation of cytochrome c oxidase and suppression of pro-apoptotic protein levels (232). In clinical (233,234) and experimental (162,235) randomized trials, participants with severe sepsis receiving GC treatment had, in comparison to controls, a significant reduction in (i) circulating nitric oxide levels (162,233,235), and (ii) spontaneous release of hydrogen peroxide (H 2 O 2 ) by neutrophils (234).…”
Section: Oxidative Stress and Circimentioning
confidence: 99%
“…Bouazza et al [127] hypothesised that the combination of APC and steroids would be beneficial compared with their individual use in resuscitated septic shock induced by caecal ligation and puncture. They observed that either APC or dexamethasone improved arterial contractility and endothelial dysfunction resulting from septic shock; however, their combination increased survival, thus recommending the re-evaluation of the combined use of APC and steroids.…”
Section: Experimentalsmentioning
confidence: 99%
“…The fact that NO and superoxide was assessed in aorta instead of mesenteric arteries constitutes a limitation of the study. Although both vascular beds depend on different regulatory mechanisms, we have previously shown that sepsis induced the same kind of hyporeactivity to Phe in aorta and small mesenteric arteries [ 6 , 41 ]. Finally, septic shock is a systemic syndrome, in which vascular inflammation, oxidative and nitrosative stresses are ubiquitous, as we showed in our previous studies [ 42 46 ].…”
Section: Discussionmentioning
confidence: 99%